The relationship between blood lipid and risk of psoriasis: univariable and multivariable Mendelian randomization analysis - Zhang, Zeng-Yun-Ou; Jian, Zhong-Yu; Tang, Yin; Li, Wei (Frontiers in Immunology, 2023)
Background: Psoriasis is an immune-mediated chronic inflammatory skin disorder. Dyslipidemia may be a risk factor of psoriasis. But the causal relationship between psoriasis and blood lipid still remains uncertain. Methods: The two data of blood lipid were obtained from UK Biobank (UKBB) and Global Lipid Genetics Consortium Results (GLGC). The primary and secondary data were from a large publicly available genome-wide association study (GWAS) with more than 400,000 and 170,000 subjects of European ancestry, respectively. The psoriasis from Finnish biobanks of FinnGen research project for psoriasis, consisting of 6995 cases and 299128 controls. The single-variable Mendelian randomization (SVMR) and multivariable Mendelian randomization (MVMR) were used to assess the total and direct effects of blood lipid on psoriasis risk. Results: SVMR estimates in primary data of blood lipid showed low-density lipoprotein cholesterol (LDL-C) (odds ratio (OR): 1.15, 95% CI: 1.04−1.26, p = 0.006 in stage 3) and triglycerides (TG) (OR: 1.14, 95% CI: 1.05−1.24, p = 0.002 in stage 3) had a highly robust causal relationship on the risk of psoriasis. However, there had no robust causal associations between high-density lipoprotein cholesterol (HDL-C) and psoriasis. The SVMR results in secondary data of blood lipid were consistent with the primary data. Reverse MR analysis showed a causal association between psoriasis and LDL-C (beta: -0.009, 95% CI: -0.016− -0.002, p = 0.009) and HDL-C (beta: -0.011, 95% CI: -0.021− -0.002, p = 0.016). In MVMR of primary data of blood lipid, the LDL-C (OR: 1.08, 95% CI: 1.02–1.15, p = 0.012 in stage 3) and TG (OR: 1.07, 95% CI: 1.01–1.13 p = 0.015 in stage 3) positively correlated with psoriasis. The results of the secondary analysis were consistent with the results of primary analysis. Conclusions: Mendelian randomization (MR) findings provide genetic evidence for the study of the pathogenic mechanism of psoriasis caused by blood lipid.